Increased ratio of summer to winter deaths due to climate warming in Australia, 1968–2018 - Hanigan, Ivan C.; Dear, Keith B.G.; Woodward, Alistair (Australian and New Zealand journal of public health, 2021)
To determine if global warming has changed the balance of summer and winter deaths in Australia. Counts of summer and winter cause‐specific deaths of subjects aged 55 and over for the years 1968–2018 were entered into a Poisson time‐series regression. Analysis was stratified by states and territories of Australia, by sex, age and cause of death (respiratory, cardiovascular, and renal diseases). The warmest and coldest subsets of seasons were compared. Warming over 51 years was associated with a long‐term increase in the ratio of summer to winter mortality from 0.73 in the summer of 1969 to 0.83 in the summer of 2018. The increase occurred faster in years that were warmer than average. Mortality in the warmest and coldest times of the year is converging as annual average temperatures rise. If climate change continues, deaths in the hottest months will come to dominate the burden of mortality in Australia.